2015
DOI: 10.1080/1034912x.2014.984590
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence and Temperament in Children with Chronic Orthopaedic Disability

Abstract: The aim of the study was to investigate social competence in children with orthopaedic disability and its concurrent relations to child's temperament, health condition, and maternal warmth. Participants were 68 Turkish children (mean = 5.94 years) with chronic orthopaedic disability and their mothers coming from disadvantaged backgrounds. Mother ratings were used to measure social competence, temperament, general health condition, and parental warmth. The attending physician rated the severity of orthopaedic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Hartup (1988) noted the consequences of a lack of appropriate and effective social skills: "the single best childhood predictor of adult adaptations is not school grades, and not classroom behavior, but rather, the adequacy with which the child gets along with other children" (p. 1). The severity and onset of the developmental disability also play a considerable role in children's overall social competence abilities (Yagmurlu & Yavuz, 2015).…”
Section: Impact Of Developmental Disabilities On Social Competencementioning
confidence: 99%
“…Hartup (1988) noted the consequences of a lack of appropriate and effective social skills: "the single best childhood predictor of adult adaptations is not school grades, and not classroom behavior, but rather, the adequacy with which the child gets along with other children" (p. 1). The severity and onset of the developmental disability also play a considerable role in children's overall social competence abilities (Yagmurlu & Yavuz, 2015).…”
Section: Impact Of Developmental Disabilities On Social Competencementioning
confidence: 99%
“…One such factor is the presence of a disability, as research indicates that children with disabilities face challenges regarding social and emotional competence. These disabilities include learning disabilities (Nowicki, 2003), attention-deficit hyperactivity disorder (Semrud-Clikeman & Schafer, 2000), orthopedic disabilities (Yagmurlu & Yavuz, 2015), autism spectrum disorder (American Psychological Association, 2013), specific language impairment (McCabe & Meller, 2004), and emotional disturbance (Algozzine, 2017). Interventions to ameliorate social and emotional deficits include, but are not limited to, direct instruction, modeling, and prompting strategies (Guralnick, 2010).…”
Section: Chapter I: Overview Of the Studymentioning
confidence: 99%
“…Other research has shown that many other children who have Individualized Education Programs (IEPs) or 504 Plans also may have difficulties in social competence, including children with ADHD (Thorell & Rydell, 2008), autism spectrum disorder (American Psychological Association, 2013), specific language impairment (McCabe & Meller, 2004), psychiatric disorders (Matthews et al, 2016;Perren & Alsaker, 2009), and physical disorders (Yagmurlu & Yavuz, 2015). Deficits in social competence have been linked to peer rejection.…”
Section: Social Competencementioning
confidence: 99%